Statistical Committees and Establishment of Museums in Russia during Late 19th to Early 20th Centuries - E. V. Igumnov (Научный диалог)
This article examines the activities of provincial and regional statistical committees as centers for the establishment of provincial museums in pre-revolutionary Russia. It highlights that, despite a considerable number of studies dedicated to the emergence of museum practices and the contributions of individual statistical committees to the creation and development of museums, this topic has yet to undergo systematic investigation. The formation of museum collections and the emergence of a network of museums affiliated with statistical committees are traced, beginning with the first museums established by the Vladimir and Arkhangelsk committees and concluding with the unsuccessful attempts to open museums by the Nizhny Novgorod, Saratov, and Transbaikal statistical committees. Common features in the development of provincial museums and the specific organizational characteristics of those associated with statistical committees are identified. The article emphasizes the classification of statistical committees as state-type institutions and clarifies the specialized focus of museum activities. Particular attention is paid to the reasons for the reorganization and separation of museums from statistical committees in the late 19th to early 20th centuries. Based on the examined sources, it is established that many museums previously under the auspices of statistical committees transitioned to scientific societies, archival commissions, and specially created committees.